2019
DOI: 10.1097/pas.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Anal and Perianal Squamous Cell Carcinomas and Their Relationship to Human Papillomavirus

Abstract: Anal squamous cell carcinomas (ASCCs) frequently harbor human papillomavirus (HPV), most commonly high-risk (HR-) HPV type 16. While p16 immunohistochemistry (IHC) is typically used as a surrogate for HR-HPV status in the oropharynx and cervix, its overexpression can also occur as a result of oncogenic stress and sometimes prove nonspecific. There have been recent investigations into the use of HPV RNA in situ hybridization (RISH) assays as an alternative method, which have shown robust results for squamous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…On the other hand, labial squamous cell carcinoma was negative (14). Moreover, it was used in anal intraepithelial and anal squamous cell carcinoma, where both of them were positive, in concordance with previous works (15,16). Furthermore, our results showed that it can be applied in patients with oropharyngeal squamous cell carcinoma, where its cellular expression was predominantly patchy to negative stain, indicating that these lesions where mostly HPV independent (17).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, labial squamous cell carcinoma was negative (14). Moreover, it was used in anal intraepithelial and anal squamous cell carcinoma, where both of them were positive, in concordance with previous works (15,16). Furthermore, our results showed that it can be applied in patients with oropharyngeal squamous cell carcinoma, where its cellular expression was predominantly patchy to negative stain, indicating that these lesions where mostly HPV independent (17).…”
Section: Discussionsupporting
confidence: 90%
“…Most cancers of the anal and perianal region are squamous cell carcinomas (SCC), predominantly HPV-related [1][2][3][4]. Previous publications have reported rare occurrences of anal carcinomas (AC) with "adenoid cystic carcinoma-like" or "cylindroma-like" histologic features, including dense hyaline inclusions of basement membrane material within tumor lobules resembling cutaneous cylindroma [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that ASC is related to HPV infection ( 4 , 5 ). Thus, to further evaluate the adequacy of our cohort, we assessed the protein expression of p16 INK4a (p16) in the primary lesions as a surrogate of HPV infection status ( 53 57 ). The p16 IHC stain was available for assessment in 67 cases, and most cases (92.5%, 62/67) were positive.…”
Section: Resultsmentioning
confidence: 99%